Estimation of gasification kinetics of coal char fines in steam ambience. (2022) - Prabhakar, Ashok; Kumar Gupta, Abhishek; Kumar Sadhukhan, Anup; Gupta, Parthapratim
Abstract: The isothermal gasification investigation of Indian sub-bituminous coal (SBC) char fines (150–180 µm) is carried out in steam ambience (11 lpm) at various reactor temperature (855–925 °C). The isothermal mass loss apparatus is used for experimentation. The time taken for 60 % conversion for 855, 890 and 935 °C are 800 s, 600 s and 420 s, and the influence is quite significant. The higher reactor temperature favours the char conversion profile and it can be seen from the conversion versus time plot. Three different kinetic models namely: VRM (Volume Reaction Model), SCM (Shrinking Core Model) and RPM (Random Pore Model) have been considered to estimate the kinetic parameters using the experimental findings. The activation energy for VRM, SCM and RPM are found to be 127, 117 and 101 kJ/mol. Random pore model is observed to give better fitting of experimental data as compared to the VRM and SCM.